Chronic constipation in Turkish children: clinical findings and applicability of classification criteria - Aydoğdu, Sema; Cakir, Murat; Yüksekkaya, Hasan Ali; Arikan, Ciğdem; Tümgör, Gökhan; Baran, Maşallah; Yağci, Raşit Vural (The Turkish Journal of Pediatrics, 2009)
We aimed to evaluate general features of children with chronic constipation and classified them according to the Iowa criteria and Rome II criteria in order to analyze applicability of these criteria in our population. The medical records of 485 children who were referred for chronic constipation over a six-year period were evaluated retrospectively. We found that 7.7% of the cases had an organic pathology, and short segment Hirschsprung disease was the leading cause. Other children (92.3%) were classified as functional constipation, with a mean age of 6.4 +/- 4 years and with slight male dominance. Encopresis was found in 117 children (51.7%) aged over four years, and was associated with older age, male predominance and long duration of symptoms. Both of the classification systems showed a similar prevalence of constipation, but 9.9% of the children with pediatric constipation were not recognized by Rome II criteria. Additionally, 1.8% of the children were not recognized by either Iowa or Rome criteria. Functional constipation is common in primary care, and most of the children were school-aged. Constipation associated with encopresis and nutritional problems such as obesity is less common in developing countries. Rome II criteria are too restrictive and do not recognize approximately 12% of the children. A new classification system must be simple, easy to understand especially by the primary care physician, and must include the common features of constipation recognized by the parents.